Individual uromodulin serum concentration is independent of glomerular filtration rate in healthy kidney donors - Enko, Dietmar; Meinitzer, Andreas; Scherberich, Jürgen E.; März, Winfried; Herrmann, Markus; Artinger, Katharina; Rosenkranz, Alexander R.; Zitta, Sabine (Clinical chemistry and laboratory medicine, 2021)
Objectives The mucoprotein uromodulin is considered to correlate with glomerular filtration rates (GFR) in patients with chronic kidney disease (CKD). Here we investigated how serum uromodulin is associated with measured GFR using inulin-clearance and GFR estimated by CKD-EPI (Chronic Kidney Disease Epidemiology Collaboration) equation in healthy subjects. Methods We assessed possible correlations between uromodulin serum concentrations, inulin-GFR and CKD-EPI-GFR in a well characterized study cohort of 112 healthy living kidney donors with two kidneys before and 64 with one kidney after kidney donation. A subgroup of 32 individuals, which presented data before and after nephrectomy, was assessed separately. Results All 112 healthy living kidney donors with two kidneys revealed individual serum uromodulin concentrations between 60.1 and 450.5 µg/L. Sixty-four healthy kidney donors after nephrectomy had significantly lower median (interquartile range) serum uromodulin concentrations (124 [101-166] vs. 185 [152-238] µg/L), inulin-GFR (67.3 [60.6-74.6] vs. 93.5 [82.1-104.4] mL/min/1.73 m 2 ), and CKD-EPI-GFR (61.2 [53.1-69.7] vs. 88.6 [80.0-97.1] mL/min/1.73 m 2 ) as compared to the 112 donors before donation (p<0.001). The subgroup of 32 subjects, which presented data before and after nephrectomy, showed almost the same pattern of kidney function. No statistically relevant associations were found between serum uromodulin and inulin-GFR or CKD-EPI-GFR regarding this healthy population. Conclusions These novel findings indicate that - in contrast to patients with CKD - serum uromodulin concentrations are not correlated with measured and estimated GFR in healthy individuals.